NIR regeneration and visible luminescence modification in photochromic glass: A novel encryption and 3D optical storage medium - Heping Zhao; Yuewei Li; Chao Mi; Yingzhu Zi; Xue Bai; Asif Ali Haider; Yangke Cun; Anjun Huang; Yue Liu; Jianbei Qiu; Zhiguo Song; Jiayan Liao; et al. (InfoMat, 2024)
Abstract Photochromic glass shows great promise for 3D optical information encryption and storage applications. The formation of Ag nanoclusters by light irradiation has been a significant development in the field of photochromic glass research. However, extending this approach to other metal nanoclusters remains a challenge. In this study, we present a pioneering method for crafting photochromic glass with reliably adjustable dual‐mode luminescence in both the NIR and visible spectra. This was achieved by leveraging bimetallic clusters of bismuth, resulting in a distinct and novel photochromic glass. When rare‐earth‐doped, bismuth‐based glass is irradiated with a 473 nm laser, and it undergoes a color transformation from yellow to red, accompanied by visible and broad NIR luminescence. This phenomenon is attributed to the formation of laser‐induced (Bi+, Bi0) nanoclusters. We achieved reversible manipulation of the NIR luminescence of these nanoclusters and visible rare‐earth luminescence by alternating exposure to a 473 nm laser and thermal stimulation. Information patterns can be inscribed and erased on a glass surface or in 3D space, and the readout is enabled by modulating visible and NIR luminescence. This study introduces a pioneering strategy for designing photochromic glasses with extensive NIR luminescence and significant potential for applications in high‐capacity information encryption, optical data storage, optical communication, and NIR imaging. The exploration of bimetallic cluster formation in Bi represents a vital contribution to the advancement of multifunctional glass systems with augmented optical functionalities and versatile applications.